Diversidade, biomassa aérea e estimativa do estoque de carbono em plantas da caatinga em um remanescente serrano no trópico semi-árido - Souza, Bruno Cruz de (2009)
Among the remaining existing mountainous areas have not yet been characterized for their composition and structure, it is believed that these remnants harbor a high biological diversity. Seeking to expand the knowledge phytoecological caatinga, particularly mountainous areas, this study assessed the species richness, diversity and plant community structure present and, through mathematical models propose drawing the allometric equation for estimating carbon stock in plants of the caatinga. The location of the study was the Serra da Arara in the municipality of São João do Cariri micro Cariri West. The land use history showed that there occurred 40 years extraction of firewood and currently the vegetation is retained. To phytosociological sampling was adopted the usual inclusion criteria for this type 11 of vegetation, characterized by the method of point-and-quadrant, which consisted of randomly selecting 30 sample units, and each plant chosen 6-point. The calculated parameters of diversity were the index of Shannon diversity, richness of taxa, equitability and richness estimators nonparametric Chao 1 and Jackknife 1. For structural analysis were determined by the total density and basal area, and the species in diameter classes and high, estimated to determine the projection area and canopy biomass was used the allometric equations, Copa (m2) = 0 , 1939 x diameter (cm) 1.6311 and Biomass Kg = 0.2627 DAP 1.9010. To elaborate the allometric equation of carbon stock, depending on the measures and DNS HT were tested regression models simple and multiple linear, logarithmic, exponential, geometric and power function. All data were processed by the software Native forest 2 and Bioestat 5.0. It was recorded 32 species in 11 families who had a rate of taxon richness and diversity of 4.86 Shannon 2.71. Values considered high when compared with work done on other studies of caatinga. The structural parameters showed low values, density (2.395 planta/ha-1), basal area (6.69 m2/ha-1), average height and diameter (3.52 and 8.67 cm), crown area ( 5872 m2 ha-1) and biomass (16.3 kg ha-1). The dominant species were the shrub layer, confirming that the vegetation in Old Cariris presents a face-sized specimens with "low" and are distributed in a scattered way, it is open, however, their diversity is high probably because we it is a mountainous area, indicating that these areas are conserved and thus play role of buffer zones for these locations. After testing the equation modeling carbon stock, it was observed that the variable total height (HT) when evaluated alone showed low values for the coefficient of determination R2 is not recommended for estimating carbon stock (CS). DNS showed the best correlation with the CS, however, the values obtained for the coefficient of determination were insufficient and can explain only 40% of variations. The combination of the DNS with HT resulted in improvement in the value of the coefficient. The models that were best suited to the type potency (CS = a DNS b) and linear regression and multiple (CS = a + bX), however, the small sample did not arrive at an equation for greater accuracy, which allow us to estimate the potential carbon storage in plants of the caatinga.